Leveraging individual differences to understand grounded procedures. (18th February 2021) - Fetterman, Adam K.; Robinson, Michael D.; Meier, Brian P.
Abstract: We applaud the goals and execution of the target article, but note that individual differences do not receive much attention. This is a shortcoming because individual differences can play a vital role in theory testing. In our commentary, we describe programs of research of this type and also apply similar thinking to the mechanisms proposed in the target article.